BACTERIOLOGICAL ANALYSIS OF CATFISH (Clarias gariepinus) IN OWO AREA, ONDO STATE, NIGERIA - A.O, Egbebi,; A.A, Muhammad,; M., Ugbodaga,; M.O, Oyama, (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
A total of eight catfish (Clarias gariepinus) were collected from different fishponds in Iyere and Otapete areas of Owo local government in Ondo State. The skin, gills, and intestines of the fish were investigated for presence of bacteria. The species of bacteria isolated from the fish samples and their percentage occurrence include Serratia spp. (2%), Salmonella spp. (32%), Escherichia coli (24%), Proteus spp. (3%), Enterococcus spp. (7%), Staphylococcus spp. (9%), Streptococcus spp. (9%), Klebsiella spp. (3%), Bacillus spp. (6%) and Pseudomonas spp. (5%). The highest microbial count (total viable count) from Clarias gariepinus was 6.5 x 102 CFU/ml from skin samples, 3.5 x 107 CFU/ml from gill samples, and 4.5 x 102 CFU/ml from intestine samples. Correspondingly, the highest microbial count (total coliform count) recorded was 7.0 x 102 CFU/ml from skin samples, 2.5 x 103 CFU/ml from gill samples, and 3.0 x 101 CFU/ml from intestine samples. Finally, the highest microbial count (total anaerobic count) from Clarias gariepinus was 2.0 x 102 CFU/ml from skin samples, 2.5 x 104 CFU/ml from gill samples, and 2.5 x 102 CFU/ml from intestine samples. The occurrence of such isolated bacteria if not properly checked could endanger both the fish and the ultimate consumers particularly if the fish harvested from these farms are undercooked.